CT FEATURES OF ADRENAL MASSES IN SRINAGARIND HOSPITAL - PHUTTHARAK, Warinthorn; SRINAKARIN, Jiraporn; CHAMADOL, Nittaya; PONGCHAIYAKUL, Chatlert; MITRCHAI, Jumpol (The ASEAN Journal of Radiology, 2023)
Abdominal CT findings of 13 adrenal massses in 13 patients who had pathologically proven were reviewed. There were 4 cortical adenomas (3 Cushing’s adenomas, | primary aldosteronism or Conn’s adenoma) and 9 nonadenomas (4 pheochromocytomas, 2 adrenal cysts, | macronodular hyperplasia, 2 cortical carcinomas). Adrenalectomy were performed in all cases. All masses of cortical adenomas had smooth contour, size less than 5S cm., homogeneous density (less amount of attenuation number) and enhancement (mild to moderate degree). All pheochromocytomas had the same clinical presentation with smooth contour of masses, size less than 5 cm. and mainly had inhomogeneous density including enhancement pattern (moderate to marked degree). One from 2 cases of adrenal cysts and | macronodular hyperplasia could mimic adrenal tumor. All 2 cases of cortical carcinoma had large size masses , more than 5 cm. : | case had typical thick irregular rim enhancement and another case similar to benign tumor exceptional for the large size.